ЭКОЛОГИЯЛЫҚ ЗАҢНАМАНЫ БҰЗҒАНЫ ҮШІН ЗАҢДЫҚ ЖАУАПКЕРШІЛІК ҰҒЫМЫ ЖӘНЕ ЖАЛПЫ СИПАТТАМАСЫ (Journal of actual problems of jurisprudence, 2019)
Conception and general characteristics of juridical responsibility for ecological infringement of legislation has been investigatedin the article.